‘What we have lost is patients who can’t handle the information’ – information misuse and open record access - Lyckblad, Camilla (Information research, 2025)
Introduction. This paper aims to broaden the understanding of information misuse by drawing on findings from an ongoing study investigating how open record access in paediatric psychiatry influences documentation practices. It explores the boundaries of what constitutes information misuse, raising the question: can individuals misuse their own information? Method. Semi-structured interviews with fifteen paediatric psychiatry clinicians experienced in open record access documentation were used as a basis for conceptual discussion on the notion of information misuse. Analysis. Conceptual discussion based on thematic analysis of interview transcripts. Results. Informants described situations regarding both clinicians’ and patients’ information behaviours that are highlighted as possible instances of authorised information misuse extending beyond malicious intent or personal gain, broadening the concept’s boundaries beyond descriptions in current research. Conclusion. Findings indicate that the concept of information misuse is far more nuanced than current research often assumes. An action deemed misuse in one context might be considered best practice in another, emphasising that the distinction between information use and misuse is heavily influenced by context and the consequences of the action.